Architecture of the global navigation satellite system for maritime applications - Dimov Stojce Ilcev (Universitas Ahmad Dahlan, 2020)
This paper introduces architecture of the global navigation satellite system (GNSS) networks in the function of the maritime space communications, navigation and surveillance (CNS) for enhanced navigation and positioning of vessels deploying passive, active and hybrid global determination satellite systems (GDSS) networks. These GNSS networks have to enhance safety and control oceangoing ships in navigation across the ocean and inland waters, to improve logistics and freight of goods, security of crew and passengers onboard ships. The maritime GNSS networks integrated with geostationary earth orbit (GEO) satellite constellations are providing important global satellite augmentation systems (GSAS) architecture, which is established by two first generations known GNSS as GNSS-1 infrastructures. The GNSS-1 network is the composition of two subnets such as the US global position system (GPS) and Russian global satellite navigation system (GLONASS). Both GNSS-1 networks play a significant contribution in very precise timing, tracking, guidance, determination and navigation of the oceangoing ships. At this point, both GNSS-1 networks, GPS and GLONASS, are used in maritime and many other mobile and fixed applications to provide enhanced accuracy and high integrity monitoring usable for positioning of the oceangoing ships. To provide improvements of GNSS-1 network it will be necessary to carry out their augmentation within several regional satellite augmentation systems (RSAS) as integration parts of GSAS infrastructures.